2021
DOI: 10.1021/acs.energyfuels.0c04213
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Engineering of Building Blocks to Synthesize a Three-Dimensional Architecture of Pd Aerogel as a Robust Self-Supporting Catalyst toward Ethanol Electrooxidation

Abstract: Although plenty of research studies have extensively focused on the synthesis of electrocatalysts with diverse methods, the synthesis of a high-performance electrocatalyst by a green and efficient method has still remained a vital problem that can seriously hamper the commercialization of fuel cell technology. Metallic aerogels recently appeared as a promising state-of-the-art class of self-supported architecture electrocatalyst materials because of their great electrocatalytic activity and enhanced stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…As illustrated, electrocatalysis of EtOH generates two strong peaks in the forward and reverse sweeps. The first peaks were generated because of the decomposition of EtOH molecules at the surface of four samples. , These interactions not only delivered the high current density but also produced the carbonaceous intermediates . Hence, other peaks appeared in backward scans because of the elimination of produced carbonaceous intermediates.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As illustrated, electrocatalysis of EtOH generates two strong peaks in the forward and reverse sweeps. The first peaks were generated because of the decomposition of EtOH molecules at the surface of four samples. , These interactions not only delivered the high current density but also produced the carbonaceous intermediates . Hence, other peaks appeared in backward scans because of the elimination of produced carbonaceous intermediates.…”
Section: Resultsmentioning
confidence: 98%
“…Hence, other peaks appeared in backward scans because of the elimination of produced carbonaceous intermediates. Subsequently, it can be logically concluded that the current density ratio generated in the forward ( J f ) to reverse ( J b ) scans can be used as a reliable parameter to evaluate the power of an electrocatalyst. , By comparing the achieved plots, the Pd 92 Co 8 aerogel ( J f / J b = 1.17), Pd 95 Co 5 aerogel ( J f / J b = 1.13), and Pd 89 Co 11 aerogel ( J f / J b = 0.96) reveal a stronger tolerance to poisoning relative to Pd/C ( J f / J b = 0.6). Additionally, the decomposition reaction of EtOH for Pd 92 Co 8 aerogel (−0.548 V), Pd 95 Co 5 aerogel (−0.538 V), and Pd 89 Co 11 aerogel (−0.532 V) started at a more negative potential in comparison to Pd/C (−0.460 V), corroborating the improved kinetics for these resultant 3D superstructures. , Moreover, the Pd 92 Co 8 aerogel, Pd 95 Co 5 aerogel, Pd 89 Co 11 aerogel, and Pd/C generated the mass activity of 4302.1, 3380.9, 2135.1, and 1007.9 mA/mg Pd .…”
Section: Resultsmentioning
confidence: 99%
“…These shoulders were generated because of the decomposing CH 3 CH 2 OH molecules on the surface of Pt–Ag and Pd–Ag aerogels. The interaction of CH 3 CH 2 OH molecules with the surface of both aerogels not only provides high current density but also generates some carbonaceous intermediates. Hence, these incomplete interactions lead to the appearance of other distinct shoulders during backward scans due to the decomposition of generated intermediates. Therefore, a strong electrocatalyst should have a high forward/backward ( J f / J b ) ratio. Measurement of this ratio ( J f / J b ) gives values of 0.6, 2.67, and 1.38 for Pd/C, Pt–Ag aerogel, and Pd–Ag aerogel, respectively. This indicates that both aerogels have greater tolerance to poisoning relative to Pd/C.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the fact that Pd is more active in an alkaline electrolyte relative to Pt. Furthermore, the mass activities relevant to Pt and Pd-based electrocatalysts for the cleavage of CH 3 CH 2 OH molecules were compared with those of Pt–Ag aerogel (Figure c) and Pd–Ag aerogel ,, (Figure d). As illustrated, Pt–Ag and Pd–Ag aerogels provide higher mass activities for the decomposition of CH 3 CH 2 OH molecules relative to other electrocatalysts.…”
Section: Resultsmentioning
confidence: 99%
“…The single Pd-based catalyst has the drawback of catalytic activity loss caused by the aggregation of Pd particles. As reported by Yi et al before, alloying Pd with Ru can perform much higher catalytic activity by adjusting the electronic structure of materials through geometric and ligand effects. To develop noble metal alloy aerogels with better activity, some new strategies should be explored.…”
Section: Introductionmentioning
confidence: 99%